Preparation and Characterization of Ba-Alginate Microspheres Containing Ovalbumin - Hariyadi, Dewi Melani; Hendradi, Esti; Irawan, Mukhlis Bayu (Jurnal Farmasi Indonesia, 2016)
The use of microspheres nowadays is important in the pharmaceuticals formulation. The aim of the present research was to evaluate physical characteristics of ovalbumin-loaded alginate microspheres using aerosolisation technique at various concentrations of alginate and BaCl2. Alginate microspheres were characterized in terms of encapsulation efficiency, yield, particle size, surface morphology and protein integrity. The comparative study between concentrations of BaCl2 and alginate polymer was investigated. Increasing concentration of alginate polymer from 2.5 to 3.5% reduced their particle size and formed smoother and spherical microspheres. Increasing Ba2+ concentration, simultaneous increased the encapsulation efficiency and yield. Scanning electron microscope (SEM) photomicrographs revealed that with the increase in the electrolyte concentration the density of the cross link is also increased. Smoother surface was demonstrated when the electrolyte concentration is increased from 0.5M to 0.75M. Formula prepared using 0.75M BaCl2 and 3.5% alginate polymer resulted the highest encapsulation efficiency (92%), the highest microspheres yield (73%) and the smallest microspheres size (3.73Âµm). Most of the formulations maintain the integrity of ovalbumin after 2 hours incubation in pH 1.2 followed by 8 hours incubation in pH 7.4. The different formulations produced different physical characteristics of ovalbumin-loaded alginate microspheres.